A Noninferiority Analysis of 3‐ vs 2‐Incision Techniques for Hypoglossal Nerve Stimulator Implantation. (30th November 2021) - Kent, David T.; Chio, Eugene G.; Weiner, Jordan S.; Heiser, Clemens; Suurna, Maria V.; Weidenbecher, Mark
Abstract : Objective: The only hypoglossal nerve stimulation (HNS) device available for US clinical use is implanted through 3 incisions. A recently proposed 2‐incision modification moved the respiratory sensing lead from the fifth to the second intercostal space to eliminate the third lower chest incision. This study compared perioperative data and therapeutic outcomes between the techniques. Study Design: Noninferiority cohort analysis of a retrospective and prospective registry study. Setting: Tertiary care and community surgical centers. Methods: Patients with obstructive sleep apnea underwent HNS implantation via a modified 2‐incision technique (I2 ). A cohort previously implanted via the standard 3‐incision technique (I3 ) were 1:1 propensity score matched for a noninferiority analysis of postoperative outcomes. Results: There were 404 I3 patients and 223 I2 patients across 6 participating centers. Operative time decreased from 128.7 minutes (95% CI, 124.5‐132.9) in I3 patients to 86.6 minutes (95% CI, 83.7‐97.6) in I2 patients ( P <. 001). Postoperative sleep study data were available for 76 I2 patients who were matched to I3 patients. The change in apnea‐hypopnea index between the cohorts was statistically noninferior (a priori noninferiority margin: 7.5 events/h; mean difference, 1.51 [97.5% CI upper bound, 5.86]). There were no significant differences between the cohorts for baseline characteristics, perioperative adverse event rates, or change in Epworth Sleepiness Score ( P >. 05). Conclusion: In a multicenter registry, a 2‐incision implant technique for a commercially available HNS device had a statistically noninferior therapeutic efficacy profile when compared with the standard 3‐incision approach. The 2‐incision technique is safe and effective for HNS implantation.